Discovery of Lake Sinai virus and an unusual strain of acute bee paralysis virus in West African apiaries - (:unkn) unknown (My University, 2016)
AbstractSamples of bees and honey from 101 apiaries were collected in the West African Republic of Benin. Visual inspection revealed high Varroa destructor and Aethina tumida infestations and low Oplostomus fuligineus infestations. A pathogen screen based on bacterial/fungal cultures or microscopic examinations revealed the absence of American and European foulbrood, chalkbrood disease, acariosis and nosemosis. However, 13 bee samples (15.47 %) were found to be infected by viruses as determined by PCR-based techniques. Acute bee paralysis virus (ABPV; 8.33 %) and Black queen cell virus (4.76 %) were the most common. From the former we found a strain with an unusual molecular signature of the capsid region, which was taxonomically positioned between ABPV and Israeli acute paralysis virus. We also discovered Lake Sinai virus (LSV; 3.57 %) for the first time in Africa. Eight honey samples collected in regions where cotton was cultivated were subjected to multi-residue and quality control analyses.
Keywords: African Research